PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Pada Lembaga Kursus dan Pelatihan di Kabupaten Jember) - Yuliastutik, Lilik; Samiadji, Samiadji; Suharto, Suharto (Manajemen & Bisnis Jurnal, 2020)
The purpose of this study is to analyze the influence of organizational culture on employee performance at LKP in Jember Regency, the influence of leadership style on employee performance at LKP in Jember Regency, the influence of organizational culture and leadership style on employee performance at LKP in Jember Regency. The method of analysis in this study uses preliminary analysis, multiple regression analysis and hypothesis testing. The results of the study that there is a positive influence of leadership on employee performance is accepted, there is an influence of organizational culture on employee performance is rejected.